(331) the interrelation of social and economic development and the problem of ''balance''. العلاقة المتبادلة بين التنمية الاجتماعية والاقتصادية ومشكلة "التوازن". - Hamza, M. (The Institute Of National Planning., 2018)
the social trends often merge with economic trends. in fact, the separation between the ''social'' and the ''economic'' is often and artifact of academic analysis and government departmentalization, analysis or administration, but the different aspects must be put together again.